2014
DOI: 10.1038/cdd.2014.96
|View full text |Cite|
|
Sign up to set email alerts
|

RIG-I-like helicases induce immunogenic cell death of pancreatic cancer cells and sensitize tumors toward killing by CD8+ T cells

Abstract: Pancreatic cancer is characterized by a microenvironment suppressing immune responses. RIG-I-like helicases (RLH) are immunoreceptors for viral RNA that induce an antiviral response program via the production of type I interferons (IFN) and apoptosis in susceptible cells. We recently identified RLH as therapeutic targets of pancreatic cancer for counteracting immunosuppressive mechanisms and apoptosis induction. Here, we investigated immunogenic consequences of RLH-induced tumor cell death. Treatment of murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(153 citation statements)
references
References 46 publications
(84 reference statements)
7
145
1
Order By: Relevance
“…For example, some researcher focused on the recognition of 5'-triphosphate single-stranded RNAs by RIG-I, and designed the 5'-triphosphate-siRNA (8,18,19). sensitized pancreatic cancer cells towards Fas-mediated cell killing (20). In the present study, we focused on the ionizing radiation to improve RLR agonist-induced cytotoxicity, and showed that cotreatment with RLR agonist and ionizing radiation effectively induced the cytotoxicity against cancer cells for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some researcher focused on the recognition of 5'-triphosphate single-stranded RNAs by RIG-I, and designed the 5'-triphosphate-siRNA (8,18,19). sensitized pancreatic cancer cells towards Fas-mediated cell killing (20). In the present study, we focused on the ionizing radiation to improve RLR agonist-induced cytotoxicity, and showed that cotreatment with RLR agonist and ionizing radiation effectively induced the cytotoxicity against cancer cells for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of retrospective studies carried out in human cancer patients to ascertain whether ICD-associated parameters can be used as prognostic biomarkers, have yielded contradictory results. [28][29][30][31][32][33][34][35] Possible reasons for this could be restriction to a few ICDderived biomarkers (mainly calreticulin, HMGB1 or CD73), the limited number of patients and variations related to cancer-types.…”
Section: Introductionmentioning
confidence: 99%
“…Local treatment of potentially resectable pancreatic cancers with RLH ligands that would carry a highly immunogenic form of cell death before surgery may facilitate the induction of a T-cellmediated antitumor immune response with the potential to control outgrowth of residual tumor cells (7).…”
Section: Hmgb1 and Immunogenic Cell Deathmentioning
confidence: 99%
“…The pathway involves type I interferon (IFN) (7,20) with a double action; it alerts the immune system to danger leading to activation of dendritic and effector cells, while it stops inhibition of immunosuppressive cells, such as regulatory T cells (20). Local treatment of potentially resectable pancreatic cancers with RLH ligands that would carry a highly immunogenic form of cell death before surgery may facilitate the induction of a T-cellmediated antitumor immune response with the potential to control outgrowth of residual tumor cells (7).…”
Section: Hmgb1 and Immunogenic Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation